Impact of zinc oxide on gut health, immunity, and growth in weaned piglets: exploring potential modes of action - Ng’ang’a, Zacharia Waithaka; Tous, Nuria; Ballester, Maria; Leskovec, Jakob; Jimenez-Moya, Beatriz; Beltrán-Debón, Raúl; Torrallardona, David; Tarradas, Joan (Frontiers in Veterinary Science, 2025)
Zinc oxide (ZnO) has been used at pharmacological levels to promote gut health and growth performance in the critical postweaning (PW) phase of piglets. The pharmacological use of ZnO in piglet diets has been banned in Europe and other countries due to antimicrobial resistance and environmental concerns. Therefore, understanding its mode of action, including its molecular mechanisms, is crucial for developing effective and sustainable alternatives. We investigated the mechanisms by which dietary supplementation with 3,000 mg/kg ZnO supports gut health and improves growth performance of piglets during the first 14 days PW. During the 2 weeks of trial (0–14 d PW), ZnO fed piglets had higher average daily gain (165 vs. 123 g/d; p < 0.01), and tended to have increased average daily feed intake (204 vs. 181 g/d; p < 0.1) and improved gain-to-feed ratio (0.669 vs. 0.774; p < 0.05) compared to control piglets. Feces from piglets in the ZnO group were also more consistent during the 2 weeks of trial (p < 0.01). At day 14 PW, ZnO piglets had lower calprotectin concentrations in serum (p < 0.01). Dietary ZnO downregulated several genes, involved in immune, oxidative and inflammatory responses, in jejunal (GPX2, REG3G, IL-8, IL-6, IL-22, and TGFβ1) and ileal (REG3G, IL-17A, IL-1β, and TLR2) mucosa (p < 0.05). It also downregulated the expression of the zinc transporter SLC39A4, that is associated with zinc homeostasis, in both tissues. Notably, PPARGC1A, which promotes energy production and lipid metabolism through fatty acid oxidation, was upregulated by ZnO in ileum. In conclusion, the current results suggest that high dietary levels of ZnO reduce the expression of inflammatory cytokines, the oxidative enzyme GPX2, pathogen recognition proteins, and zinc transporters while promoting the expression of PPARGC1A gene related with energy metabolism in the intestine. Therefore, ZnO can facilitate a smoother weaning transition to reduce weaning related gut health disturbances, ultimately contributing to gut homeostasis and improved performance.